2021
DOI: 10.3390/plants10102202
|View full text |Cite
|
Sign up to set email alerts
|

Boosting of Antioxidants and Alkaloids in Catharanthus roseus Suspension Cultures Using Silver Nanoparticles with Expression of CrMPK3 and STR Genes

Abstract: Global agricultural systems are under unprecedented pressures due to climate change. Advanced nano-engineering can help increase crop yields while ensuring sustainability. Nanotechnology improves agricultural productivity by boosting input efficiency and reducing waste. Alkaloids as one of the numerous secondary metabolites that serve variety of cellular functions essential for physiological processes. This study tests the competence of silver nanoparticles (AgNPs) in boosting alkaloids accumulation in Cathara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 68 publications
(80 reference statements)
0
27
0
Order By: Relevance
“…At a later stage of development, plants exposed to salinity experience increased oxidative stress because of the production of supernumerary amounts of reactive oxygen species (ROS). This results in oxidative injuries to various cellular macromolecules, such as lipids, proteins, and nucleic acids, which eventually deactivate numerous important cellular processes in plants [ 1 , 9 ]. All the major processes, such as photosynthesis, and the energy of plants are also affected by salinity stress.…”
Section: Introductionmentioning
confidence: 99%
“…At a later stage of development, plants exposed to salinity experience increased oxidative stress because of the production of supernumerary amounts of reactive oxygen species (ROS). This results in oxidative injuries to various cellular macromolecules, such as lipids, proteins, and nucleic acids, which eventually deactivate numerous important cellular processes in plants [ 1 , 9 ]. All the major processes, such as photosynthesis, and the energy of plants are also affected by salinity stress.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Frukh et al [45] observed that the accumulation of H 2 O 2 generated more MDA in rice plants under salinity stress. The relationship of an increase in H 2 O 2 content and MDA accumulation was documented by several research groups [46][47][48].…”
Section: Discussionmentioning
confidence: 90%
“…This condition leads to the expression of MAPK genes that affects transcriptional reprogramming of secondary metabolites-related genes. Interestingly, a recent study conducted by Fouad et al [49] has reported that AgNPs triggered the accumulation of alkaloids in C. roseus via ROS-mediated MAPK cascade through the up-regulation of the MAK3 gene. It leads finally to the overexpression of alkaloid biosynthetic genes.…”
Section: Possible Mechanism Of Agnps In Plant Cellsmentioning
confidence: 99%
“…Callus which is derived from plant organs cultured in vitro can be defined as unorganized or undifferentiated cell mass that can serve as a potential plant biotechnological platform to manufacture significant bioactive compounds of pharmaceutical interests [10]. In addition, callus culture coupled with nano-elicitation has been reported as a promising strategy for enhancing alkaloid [49], flavonoid, and phenolic compounds [50]. For instance, AgNPs have been reported to boost the concentration of different flavonoids including flavonols, hydroxybenzoic and hydroxycinnamic acids in the CSC of bitter gourd [21].…”
Section: Silver-nanoparticles In Crop Improvementmentioning
confidence: 99%